Dinamika Kepemimpinan Adaptif dalam Pengelolaan Layanan PAUD Holistik Integratif di KB PKK Putra Bangsa Purwosari - Arisanti, Fifi; Sulton, Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
The implementation of Holistic Integrative Early Childhood Education (ECE) services demands complex cross-sectoral synergy, which is often hindered by managerial and resource limitations, particularly in community-based institutions. This study aims to analyze the dynamics of adaptive leadership in optimizing the management of education, health, nutrition, and protection services at KB PKK Putra Bangsa Purwosari. This research employs a qualitative approach to explore the principal's managerial strategies in responding to operational challenges. The main findings indicate that adaptive leadership operates through three strategic mechanisms: (1) the principal's ability to diagnose situations to distinguish between technical and adaptive challenges; (2) the mobilization of external stakeholders (Integrated Healthcare Center, Village Midwives, and PKK Cadres) to bridge resource gaps; and (3) the distribution of authority to educators to innovate services autonomously. These dynamics have successfully transformed the organizational culture to be more responsive and resilient in serving children's comprehensive needs. The conclusion asserts that a leader's flexibility in network building and community asset mapping are fundamental elements in ensuring the sustainability and quality of Holistic Integrative ECE services amidst facility constraints.